2016
DOI: 10.1016/j.jconrel.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of magnetic drug targeting using fibered confocal fluorescence microscopy

Abstract: Magnetic drug targeting has been proposed as means of concentrating therapeutic agents at a target site and the success of this approach has been demonstrated in a number of studies. However, the behavior of magnetic carriers in blood vessels and tumor microcirculation still remains unclear. In this work, we utilized polymeric magnetic nanocapsules (m-NCs) for magnetic targeting in tumors and dynamically visualized them within blood vessels and tumor tissues before, during and after magnetic field exposure usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Our results showed that there is no aggregation with serum components up to 12 h of incubation, suggesting that this PM may be adequate for intravenous administration in vivo , since as for other micellar systems, a circulation half-life under 12 h is expected (Rijcken et al., 2007 ). Moreover, our results with in vivo FCFM imaging show that PM can be observed in circulation up to 4 h postadministration and that nanosystems are able to leave the vascular bed and extravasate into the tumor parenchyma, probably due to the presence of leaky vasculature of the tumors, as previously demonstrated by FCFM technique in animal models (Bai et al., 2016 ). This process would ensure the enhanced permeability and retention (EPR) effect (Matsumura & Maeda, 1986 ; Maeda et al., 2000 ) and would help to increase the efficacy of the siRNA.…”
Section: Discussionsupporting
confidence: 83%
“…Our results showed that there is no aggregation with serum components up to 12 h of incubation, suggesting that this PM may be adequate for intravenous administration in vivo , since as for other micellar systems, a circulation half-life under 12 h is expected (Rijcken et al., 2007 ). Moreover, our results with in vivo FCFM imaging show that PM can be observed in circulation up to 4 h postadministration and that nanosystems are able to leave the vascular bed and extravasate into the tumor parenchyma, probably due to the presence of leaky vasculature of the tumors, as previously demonstrated by FCFM technique in animal models (Bai et al., 2016 ). This process would ensure the enhanced permeability and retention (EPR) effect (Matsumura & Maeda, 1986 ; Maeda et al., 2000 ) and would help to increase the efficacy of the siRNA.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, they are easily excreted from the mice body after postinjection of several days through the urine and faeces due to the biodegradation of MSN, and the biodegradation byproducts from these MMSNs are nontoxic to the biological tissues . However, this inhibition rate by magnetic targeting is influenced by many factors, such as: the magnetic saturation of the nanocarriers, the strength of the externally applied magnetic field, the tumor type, and the tumor vascularity . So, we expect to design a more stronger magnetic nanocarrier under more stronger magnetic field to enhance the anticancer ability.…”
Section: Resultsmentioning
confidence: 99%
“…EVs have the potential to be used as natural nanoparticles carriers for delivery of therapeutic agents for disease treatment . The imaging and distribution of EVs in vivo are important for the development and optimization of EV‐based therapy, and FCFM has been shown to be suitable for in vivo imaging of polymeric magnetic nanoparticles bearing therapeutic agents within mouse blood vessels and tumors . The resolution and sensitivity of FCFM with the Cellvizio system also enables the accurate ex‐vivo detection and visualization of fluorescently labeled EVs (Figure ); therefore can therefore be used to gain knowledge of EV uptake mechanisms in vivo.…”
Section: The Applications Of Fcfm With Cellvizio System In Imaging Anmentioning
confidence: 99%